2013
DOI: 10.1021/ja4086935
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Single-Layer Two-Dimensional Honeycomb Supramolecular Organic Framework in Water

Abstract: The self-assembly of well-defined 2D supramolecular polymers in solution has been a challenge in supramolecular chemistry. We have designed and synthesized a rigid stacking-forbidden 1,3,5-triphenylbenzene compound that bears three 4,4'-bipyridin-1-ium (BP) units on the peripheral benzene rings. Three hydrophilic bis(2-hydroxyethyl)carbamoyl groups are introduced to the central benzene ring to suppress 1D stacking of the triangular backbone and to ensure solubility in water. Mixing the triangular preorganized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
311
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(327 citation statements)
references
References 67 publications
13
311
0
3
Order By: Relevance
“…Specifically, organic 2D nanomaterials hold promise as biocompatible materials that can be chemically tailored and built from the bottom up, through the self-assembly of small molecule, protein, or polymer building blocks (2)(3)(4)(5). Polymer-based 2D nanomaterials, in particular, hold promise as templates for bottom-up assembly of circuits, semiconductors, and organicinorganic composite materials (6)(7)(8) as well as high surface area membranes for filtration, catalysis, and sensing (9,10).…”
mentioning
confidence: 99%
“…Specifically, organic 2D nanomaterials hold promise as biocompatible materials that can be chemically tailored and built from the bottom up, through the self-assembly of small molecule, protein, or polymer building blocks (2)(3)(4)(5). Polymer-based 2D nanomaterials, in particular, hold promise as templates for bottom-up assembly of circuits, semiconductors, and organicinorganic composite materials (6)(7)(8) as well as high surface area membranes for filtration, catalysis, and sensing (9,10).…”
mentioning
confidence: 99%
“…To address this issue, we have begun to develop charged COPs that incorporate redox-active viologens and are capable of adsorbing iodine vapor, toxic dyes, and metal ions by anion exchange. [22,23] Despite their great potential, viologen-based COPs are still rarely documented in the literature, though Li et al [24] have reported supramolecular organic frameworks (SOFs) that contain viologen struts and form in water.…”
Section: Gobinda Dasmentioning
confidence: 99%
“…To address this issue, we have begun to develop charged COPs that incorporate redox-active viologens and are capable of adsorbing iodine vapor, toxic dyes, and metal ions by anion exchange. [22,23] Despite their great potential, viologen-based COPs are still rarely documented in the literature, though Li et al [24] have reported supramolecular organic frameworks (SOFs) that contain viologen struts and form in water.Herein, we report a one-pot, template-free solvothermal synthesis involving the Zincke reaction (Scheme 1) of two porous, viologen-linked COPs that contain pyrene derivatives as central core moieties. Both polymers exhibit outstanding chemical stability in common organic solvents, neutral water, and aqueous acid or base.…”
mentioning
confidence: 99%
“…b) Self‐assembly of different building blocks with cucurbit[8]uril in water 35c. Reproduced from Refs.…”
Section: Porous Polyelectrolyte Membranesmentioning
confidence: 99%